2007
DOI: 10.1038/sj.jhh.1002304
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells are reduced in refractory hypertension

Abstract: Circulating endothelial progenitor cells (EPCs) play a key role in the maintenance of endothelial homoeostasis and promote vascular repair. They may also be of predictive value for cardiovascular events. Reduced EPC number and functional activity have been associated with several cardiovascular risk factors, but their relationship with hypertension remains unclear. The objective of this study was to investigate if number and function of circulating EPCs are reduced in patients with refractory hypertension (RHT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 47 publications
6
32
1
Order By: Relevance
“…Moreover, a recent study by Delva et al 31 examined the number of cultured early EPCs in 36 patients with essential hypertension and 24 control subjects and did not report a reduced number of cultured early EPCs in hypertensive patients. However, in patients with advanced and refractory hypertension, EPC numbers were reduced in a recent study by Oliveras et al 32 Therefore, the observations of the present study in the context of previous findings are consistent with the notion that the dysfunction of early EPCs is rather substantially more pronounced and begins earlier as compared with a detectable reduction of the number of circulating early EPCs in patients with hypertension. Importantly, the present study provides for the first time evidence that the in vivo re-endothelialization capacity of early EPCs is already profoundly reduced in patients with prehypertension and is related to impaired endothelium-dependent vasodilation and senescence of early EPCs.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a recent study by Delva et al 31 examined the number of cultured early EPCs in 36 patients with essential hypertension and 24 control subjects and did not report a reduced number of cultured early EPCs in hypertensive patients. However, in patients with advanced and refractory hypertension, EPC numbers were reduced in a recent study by Oliveras et al 32 Therefore, the observations of the present study in the context of previous findings are consistent with the notion that the dysfunction of early EPCs is rather substantially more pronounced and begins earlier as compared with a detectable reduction of the number of circulating early EPCs in patients with hypertension. Importantly, the present study provides for the first time evidence that the in vivo re-endothelialization capacity of early EPCs is already profoundly reduced in patients with prehypertension and is related to impaired endothelium-dependent vasodilation and senescence of early EPCs.…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, hypertension has an increasingly intensified damage to EPCs with the increase of blood pressure and the development of hypertension pathogenetic process. [5] This research showed that, in comparison with the control group, the proliferation ability of peripheral blood EPCs was obviously decreased in the hypertension group, which conformed to previous studies (p < .01). [5] Furthermore, authors of this article found that, in comparison with the control group, EPCs migration and adhesion ability were also obviously decreased in the hypertension group.…”
Section: Discussionsupporting
confidence: 78%
“…[5] This research showed that, in comparison with the control group, the proliferation ability of peripheral blood EPCs was obviously decreased in the hypertension group, which conformed to previous studies (p < .01). [5] Furthermore, authors of this article found that, in comparison with the control group, EPCs migration and adhesion ability were also obviously decreased in the hypertension group. The results suggested that, not only the number of peripheral blood EPCs, but also their migration and adhesion ability were degraded under the condition of hypertension.…”
Section: Discussionsupporting
confidence: 78%
“…Further, it has also been suggested that differentiation potential of bone-marrow-derived MSCs decreases with age [11]. Recent data also indicate that EPC function is diminished in patients with severe vascular disease and multiple coronary risk factors [12,13]. …”
mentioning
confidence: 99%